Caracterização fenotípica e diversidade genética de ovinos da raça morada nova variedade branca - Nunes, Samuel Freitas (Universidade Federal Rural do Semi-Árido, 2020)
From the lack of technical information about the racial pattern of the white variety of Morada Nova sheep and the risk situation in which it is found, the present study aimed to provide information to support the selection and maintenance of genetic variability from morphometry data, zootechnical indexes, images and molecular study using SNPs markers to better understand the structure and genetic diversity of herds. Morada Nova white phenotype animals are dolichocephalic (Ice = 41.9), with good chest capacity (IT = 60.2), medium body development (CI = 0.80) and square croup (IP = 105.8 ), have depigmented or partially depigmented mucous membranes, hooves and skin and morphological characteristics (IRCG = 1.0; ICC1 = 0.6; ICC2 = 0.5; IPT = 32.4; IPL = 30.5 and IRPT = 1, 3) that indicate aptitude for meat production. Although there are some variations in these characteristics between populations, a large part can be explained by environmental factors, mainly by differences in nutritional and reproductive management. Among the related variables, cephalic measurements are those that have the greatest power of differentiation between animals. Inbreeding among individuals is low (FIS < 0.05), in contrast the genetic differentiation between most subpopulations is low (FST < 0.05), results that underscore the need to think about strategies and promotion to manage this population.
Keywords: Conservação; Genotipagem; Morfologia; Recursos genéticos animais; Variabilidade; Conservation; Genotyping; Morphology; Conservation of genetic resources; Variability; CIENCIAS AGRARIAS::MEDICINA VETERINARIA